Peningkatkan Proses Pembelajaran Tematik Dengan Menggunakan Model Pembelajaran Project Based Learning (PjBL) Di Kelas VI SD NegerI 027962 Binjai Tahun Pelajaran 2022/2023 - Ayunda Hajjah Hayati, Mustika (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This research was conducted to improve the process and results of thematic learning in class VI students at SD Negeri 027962 Binjai. Researchers apply the Project based learning (PjBL) learning model to realize these two things. This type of research is class action research (Classroom Action Research), with the research subject being Class VI Students of SD Negeri 027962 Binjai for the 2022/2023 academic year. There are 27 students, with details of 12 male students and 15 female students. The object of this research is the thematic learning process of class VIA students. This research was carried out in two learning cycles. With 4 (four) stages in each cycle, namely planning, implementation, observation/observation, and reflection. The data collection tools are tests, observation sheets, and documentation. The results of the analysis of data from 27 students obtained thematic learning outcomes for the very low category 9 students (33.33%), the low category 5 students (18.52%), the medium category 7 students (25.93%), the high category 5 students ( 18.52%), and very high category 1 student (3.70%), with a classical average of 51.11. From the results obtained above, they were followed up in cycle I using the PjBL model and obtained thematic learning results for the very low category 6 students (22.22%), the low category 4 students (14.81%), the medium category 3 students (11, 11%), high category 8 students (29.63%), and very high category 6 students (22.22%), with a classical average of 63.24%. The acquisition of cycle I significantly increased and was followed up in cycle II with the acquisition of thematic learning scores for the very low category 2 students (7.41%), the high category 11 students (40.74%), and the very high category 14 students (51.85). %), with a classical average of 78.24.